Keap1/Nrf2-independent antioxidative activity of Phyllanthus amarus extract in zebrafish - Thanh Nguyen, Vu; Nguyen, Thi Tam Thanh; Phuong Phi, Nguyen; Mai Que, Duong Nguyen; Thu Hien, Luu; Phuong Hanh, Le Luu; Phuong Thao, Ngo Huynh; Nguyen, Xuan Tong; Thanh Luu, Pham; Thuy Vy, Nguyen Hoang; Thi Thuy, Dinh (Vietnam Journal of Biotechnology, 2022)
The Keap1 protein (Kelch-like ECH-related protein 1) and the Nrf2 transcription factor (NF-E2-related factor 2) are important systems for maintaining homeostasis, redox, and metabolism. Based on the Keap1/Nrf2 pathway, the antioxidative mechanism of P. amarus extract (PAE) was predicted. In this paper, we evaluated the protective effects of PAE on the oxidative toxicity induced by sodium arsenite (NaAsO2) and hydrogen peroxide (H2O2) in zebrafish larvae. We first determined that the LC50 values for NaAsO2, H2O2, and PAE at 3.5 days postfertilization (dpf) were 1 mM, 3 mM, and 200 μg/mL, respectively. Then, to assess the antioxidant effects of P. amarus, 3.5 dpf zebrafish larvae were pretreated with PAE at concentrations of 0, 50, 75, and 100 μg/ml for 12 h, and then the PAE solution was replaced with 1 mM NaAsO2 or 3 mM H2O2 to assess challenge survival within 48 h. Interestingly, all three concentrations, 50, 75, and 100 μg/mL PAE, increased the survival rate of zebrafish larvae compared to those larvae exposed to only 1 mM NaAsO2. Similarly, PAE at concentrations of 75 and 100 μg/mL protected zebrafish larvae after exposure to 3 mM H2O2. Real-time qPCR analysis was performed after 3.5 dpf zebrafish larvae were exposed to 100 μg/mL PAE for 12 h to verify whether the increasing antioxidative activity is depended on the Nrf2 pathway. The expression of the Nrf2 target genes glutathione-S-transferase Pi 1 (gstp1) and peroxidase 1 (prdx1) was assessed using real-time qPCR. However, the expression of this gene was not significantly different between control larvae and PAE-treated larvae. Thus, PAE induces antioxidant activity in zebrafish in a Keap1/Nrf2-independent manner.